Bank Syariah Indonesia Health Status During Cyber Attack Using CAMEL: Kondisi Kesehatan Bank Syariah Indonesia Selama Serangan Siber Menggunakan CAMEL - Juliana, Rizki Intan; Nurasik (Indonesian Journal of Islamic Studies, 2025)
General Background: Bank Syariah Indonesia (BSI), formed from the merger of Bank BRI Syariah, Bank Syariah Mandiri, and Bank BNI Syariah, plays a strategic role in the Indonesian sharia banking sector. Specific Background: Recently, BSI experienced a cyber attack causing financial losses and reputational challenges over an unpredictable period. Knowledge Gap: Limited research exists examining the resilience and health level of sharia banks during cyber disruptions using structured financial assessment methods. Aim: This study analyzes BSI’s health level before and during a cyber attack using the CAMEL method. Methods: A comparative descriptive approach with quantitative analysis was employed, using secondary monthly financial reports from April and May 2023, followed by descriptive statistics, normality tests, and paired sample t-tests. Results: The findings indicate no significant difference in BSI’s health level before and during the cyber attack. Novelty: This study provides empirical evidence on the stability of sharia bank health metrics during cyber threats. Implications: The results inform bank management and regulators about the resilience of financial and operational health indicators under cyber risk conditions. Highlights: Comparative analysis of BSI health before and during a cyber attack. No significant change detected using CAMEL metrics. Provides evidence on sharia bank resilience during cyber disruptions. Keywords: BSI, CAMEL, Sharia Bank Health, Cyber Attack, Financial Resilience